(3OQQ GdSMGHI ajef ONd eUQ ef GdUMGHIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s; (3eMeO Hf GdQHjY GdLjRjs ((3jhfS GdTQfLi GdgQeRi s)
(3ChdgG (B:s
(3GdMeO ddg MeOkG cKjQkG hHYO abO Cda GdEeGe eMeO GdQHjY GdLjRi cJGHkG ai ef ONd eUQ ef GdUMGHI aChQO ajg eGFI hfjaG hbO QCjJ Cf CdNU cJGH eMeO Hf GdQHjY GdLjRi hSejJg OQQ GdSMGHI ajef ONd eUQ ef GdUMGHI MQa GdgeRI EHQgg Hf GdUHGMs
(3BNQgG (B:s
(3eMeO Hf eMeO Hf eMeO GdHZOGOi GdebQi GdRQcTi CUdg ef TjQGR eGJ ai LeGOi GdBNQI SfI NeS hYTQjf hKeGf eGjg hMSHfG Gddg hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCgdjI HHGQjS (B((3YQHi (B2016) s
Keywords: (3GdeLGejYs